Original sin - Di Novi, Denise; Guinzburg, Kate 1962-; Lees, Carol; Cristofer, Michael; Banderas, Antonio; Jolie, Angelina 1975-; Jane, Thomas; Thompson, Jack; Itzin, Gregory; Mackie, Allison; Pringle, Joan; Richards, Cordelia; et al. (MGM Home Entertainment, 2002)
A mysterious woman from Boston whose insatiable lust for her new wealthy, plantation owner husband is exceded only y her desire for his fortune.